HEALTH PROMISING EFFECTS OF POTATO PEELS AND THEIR POTENTIAL EMPLOYMENTS IN FOOD AND NUTRACEUTICAL INDUSTRIES AND NONFOOD USES FROM SUSTAINABILITY POINT OF VIEW - Mushtaq Qudsia; Timar Adrian; Joly Nicolas; Spalletta Alexis; Martin Patrick; Ishtiaq Uzair (Natural Resources and Sustainable Development)
Potato is the central vegetable crop after rice, wheat and maize having more than 5000 various varieties. Worldwide potato industry generates huge amounts of potato peel waste (PPW) approximately 70-140 thousand tones. Indecent dumping of such waste in many urban areashave resulted into contaminated environment raising health concerns. PPW is a major underutilized substrate whist it comprises many valuable compounds including starch, polysaccharide i.e., hemicellulose, cellulose and pectin, protein, lignin, lipid, fiber, ash, moisture and phenolic compounds such as vanillin, coniferyl, caffeic and ferulic acid which make it an excellent choice for various industrial sector. PPW, being a good source of valuable compounds including fiber and little protein content can be used as an exceptional ingredient in animal feed.PPW having considerable nutritional value along with bioactive and technological important properties, the sustainable processing of diverse byproducts of this waste offers great interest for pharmaceutical and food industries.